Plans for upgrading existing conventional 150 kV substations into digital substations in Sulawesi - Indonesia, accompanied by financial studies - Daniel Rio Armanda; Pawenary Pawenary (Universitas Mercu Buana, 2023)
The focus of Indonesia's G20 Presidency lies on three main pillars, one of them is transition to sustainable energy. The development of these conditions forced PLN (State Electricity Company in Indonesia) to innovate by participating in implementing the latest digitalization technology in distribution electrical energy to customers, one way to do this is by implementing the smart grid concept, which is digital substation technology, is considered capable to response the challenges of digitizing the electricity system in the energy distribution sector. Digital substation technology in Indonesia is still in development stage and there are only six pilot projects in scattered locations, hence in-depth research is needed regarding equipment requirements and the amount of investment needed by PLN to build digital substations, especially the plan for implementing digital substations in Sulawesi. One of methods for developing digital substations in Indonesia is upgrading conventional into digital substation. Research is conducted by studying and observing the existing digital substation in Indonesia. Afterwards in this paper will be explained how to upgrade and what materials, or equipment that must be equipped to upgrading conventional substations. Then, what is the actual value of the investment needed by PLN to build or upgrading into a digital substation in Indonesia, especially in Sulawesi. Furthermore, whether the upgrading plans can be declared financially feasible.